Performance of Retarding Basin in Flood Disaster Risk Mitigation in Welang River, East Java Province, Indonesia - Prorida Sari (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Flood phenomenon caused by high rainfall and sea tides on a watershed seat the tidal area, including the Welang River, commonly occur and the number of events is increasing. Construction of retarding basin is one of flood risk mitigation efforts by reducing the flood peak discharge. Assessment of flood management in Welang River was conducted with hydrology and hydraulic approaches, by using the Hydrologic Engineering Centre-Hydrologic Modelling System (HEC-HMS) 4.0 and Hydrologic Engineering Center–River Analysis System (HEC-RAS) 5.0.3 software. The hydraulic simulation consists of 4 scenarios. Scenario 1 was the current condition, while scenario 2, 3, and 4 were the retarding basin construction with one side spillway, one on the upstream (River Station (RS) 7400), on the middle (RS 6970), and on the downstream (RS 6590), respectively. The height variation of side spillways are 3 m and 4 m. Flood routing simulation result showed that the existing river channel condition could not accommodate of 2-year flood and 10-year flood, which caused peak discharge of 497.7 m3/s and 794.9 m3/s. At the RS 6590, the maximum runoff height of 2-year and 10-year flood were 0.66 and 1.02 m, respectively. Under the 2-year return period of flood, the discharge reduction caused by the retarding basin at control point RS 5341.4 (Karangketug Village), were 39.63 m3/s, 31.83 m3/s, and 41.93 m3/s, respectively for scenario 2, 3 and 4 with the 3 m side spillway height and 14.71 m3/s, 16.76 m3/s, and 13.74 m3/s, respectively for scenario 2, 3 and 4 with the 4 m side spillway height.